Assessment of land surface temperature and factors influencing urban green space dynamics in Sapele, Delta State of Nigeria (2024)
Forest is a carbon sink contributing to the tropical Land Surface Temperature (LST) changes. However, information on the nexus between Urban Green Space (UGS) and LST of most cities is limited. Therefore, spatiotemporal variability in UGS and LST, and factors affecting UGS dynamics were examined in Sapele, Delta State, Nigeria. Landsat imageries of 2002, 2012, and 2022 were obtained and classified using Iso Cluster Classification with point pixel-based correction for accuracy improvement. The LST was extracted from the imageries. Relationship between NDVI and LST was established using R. Structured questionnaire was used to elucidate information on factors affecting UGS (FAUGS); population growth (PG), lack of law enforcement (LLE), demand for timber (DT), agricultural expansion (AE), overgrazing (O), soil characteristics (SC), urban sprawl (US) and lack of land tenure system (LLTS), using logit regression at α=0.05. Four LULC were identified; UGS, water bodies, bare land, and built-up areas. The UGS decreased from 88.55% in 2002 to 81.83% in 2022, built-up area expanded from 4.64% to 12.55%. Highest mean LST (27.46°C) and lowest NDVI (0.54) were recorded in 2012, least LST (26.46°C) and highest NDVI (0.69) were recorded in 2002. Negative nexus was observed between NDVI and LST for 2002 (-0.453), to 2022 (-0.393). The odd ratio showed that PG (1.2x108), US (13.8), and LLTS (3.0) significantly affected UGS dynamics with the regression model (FAUGS) = -9.7 + 18.6(PG) – 8.0(LLE) - 23.61(DT) - 18.5(AE) -10.8(O) - 25.7(SC) + 2.6(US) + 1.1(LLTS). This study affirmed that urban green space was affected by urbanization.